Developmental Proteomics Reveals the Dynamic Expression Profile of Global Proteins of Haemaphysalis longicornis (Parthenogenesis) - Min-Xuan Liu; Xiao-Pei Xu; Fan-Ming Meng; Bing Zhang; Wei-Gang Li; Yuan-Yuan Zhang; Qiao-Ying Zen; Wen-Ge Liu (Life)
H. longicornis is used as an experimental animal model for the study of three-host ticks due to its special life cycle and easy maintenance in the laboratory and in its reproduction. The life cycle of H. longicornis goes through a tightly regulated life cycle to adapt to the changing host and environment, and these stages of transition are also accompanied by proteome changes in the body. Here, we used the isobaric tags for a relative and absolute quantification (iTRAQ) technique to systematically describe and analyze the dynamic expression of the protein and the molecular basis of the proteome of H. longicornis in seven differential developmental stages (eggs, unfed larvae, engorged larvae, unfed nymphs, engorged nymphs unfed adults, and engorged adults). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of the differentially expressed proteins (DEPs) were used. In our study, A total of 2044 proteins were identified, and their expression profiles were classified at different developmental stages. In addition, it was found that tissue and organ development-related proteins and metabolism-related proteins were involved in different physiological processes throughout the life cycle through the GO and KEGG analysis of DEPs. More importantly, we found that the up-regulated proteins of engorged adult ticks were mainly related to yolk absorption, degradation, and ovarian development-related proteins. The abundance of the cuticle proteins in the unfed stages was significantly higher compared with those of the engorged ticks in the previous stages. We believe that our study has made a significant contribution to the research on H. longicornis, which is an important vector of SFTSV. In this study, we identified changes in the proteome throughout the H. longicornis development, and functional analysis highlighted the important roles of many key proteins in developmental events (ovarian development, the molting process, the development of midgut, the development and degeneration of salivary glands, etc.). The revelation of this data will provide a reference proteome for future research on tick functional proteins and candidate targets for elucidating H. longicornis development and developing new tick control strategies.